A high‐efficiency 60‐GHz indirect local oscillator in 90‐nm CMOS. Issue 9 (27th June 2016) - Byeon, Chul Woo; Park, Chul Soon
ABSTRACT: This letter presents a highly efficient 60‐GHz local oscillator (LO) in a 90‐nm CMOS. The proposed LO consists a 30‐GHz LC VCO and a frequency doubler. With this topology, the LO generator has a high output power of −0.1 dBm at 58.2 GHz, consuming only 10.4 mW from a 0.8 V supply, resulting in a record efficiency of 9.4% among 60‐GHz CMOS LOs. At 58.2 GHz, the phase noise is −115 dBc/Hz at a 10‐MHz offset. The measured frequency tuning range is from 57.56 to 64.47 GHz. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2091–2093, 2016